Ethnopharmocology, phytochemistry and pharmacology of the genus Orthosiphon: A review - Rui Wang; Ling Qiu; Qing-wen Zhang; Ligen Lin (Phytomedicine Plus)
Background: Plants of the genus Orthosiphon (Lamiaceae) have been widely employed in traditional and ethnic medicines for the treatment of various diseases, including diabetes, kidney stones, edema, rheumatism, hepatitis, hypertension, and urinary tract disorders. Purpose: This review summarized the research progresses in botany, traditional uses, phytochemistry, and pharmacological activities on plants of the genus Orthosiphon. Additionally, this review described the shortcomings of studies on these species, thus serving as the basis of further researches and development of these traditional herbal medicines. Method: Orthosiphon-related information was collected from the online databases, such as Google Scholar, SciFinder, Web of Science, Elsevier, PubMed and China Knowledge Resource Integrated (CNKI). Results: Plants of the genus Orthosiphon are widely distributed in African, Australia, South Asian, and Southeast Asian, and in China. Phytochemical investigations on Orthosiphon species have revealed the presence of various compounds, mainly including phenolic acids, flavonoids, diterpenoids, triterpenoids, sesquiterpenoids, and chromenes. Previous reports have demonstrated the diverse pharmacological properties of extracts and constituents derived from Orthosiphon, such as anti-cancer, anti-diabetic, anti-inflammatory, antioxidant, hepatoprotective, analgesic, and nephroprotective effects. However, previous researches on this genus were somewhat limited and skewed towards a few species, with a particular emphasis on O. aristatus, O. wulfenioides, O. thymiflorus and O. rubicundus (D. Don) Benth, which might be attributed to the ethnopharmacological background, geographical constraints, and the distribution of these species. In the future, more investigations on other species of the genus Orthosiphon are needed. Conclusion: This study provided a comprehensive overview of the ethnopharmacological, phytochemical, and pharmacological progresses related to the genus of Orthosiphon. Despite substantial bias in attention among various species of the genus Orthosiphon, its potential as health food and therapeutic agents is evident. The genus is an underexplored source of bioactive compounds with potential in various therapeutic areas. This review laid the groundwork for further investigation and development of these traditional herbal remedies.